Neutralizing Antibody Response and Efficacy of Novel Recombinant Tetravalent Dengue DNA Vaccine Comprising Envelope Domain III in Mice - Kulkarni, Ajit (Iran J Med Sci, 2017)
BACKGROUND: Dengue is a global arboviral threat to humans; causing 390 million infections per year. The availability of safe and effective tetravalent dengue vaccine is a global requirement to prevent epidemics, morbidity, and mortality associated with it. METHODS: Five experimental groups (6 mice per group) each of 5-week-old BALB/c mice were immunized with vaccine and placebo (empty plasmid) (100 µg, i.m.) on days 0, 14 and 28. Among these, four groups (one group per serotype) of each were subsequently challenged 3 weeks after the last boost with dengue virus (DENV) serotypes 1-4 (100 LD(50), 20 µl intracerebrally) to determine vaccine efficacy. The fifth group of each was used as a control. The PBS immunized group was used as mock control. Serum samples were collected before and after subsequent immunizations. EDIII fusion protein expression was determined by Western blot. Total protein concentration was measured by Bradford assay. Neutralizing antibodies were assessed by TCID(50)-CPE inhibition assay. Statistical analysis was performed using Stata/IC 10.1 software for Windows. One-way repeated measures ANOVA and Mann-Whitney test were used for neutralizing antibody analysis and vaccine efficacy, respectively. RESULTS: The recombinant EDIII fusion protein was expressed adequately in transfected 293T cells. Total protein concentration was almost 3 times more than the control. Vaccine candidate induced neutralizing antibodies against all four DENV serotypes with a notable increase after subsequent boosters. Vaccine efficacy was 83.3% (DENV-1, -3, -4) and 50% (DENV-2). CONCLUSION: Our results suggest that vaccine is immunogenic and protective; however, further studies are required to improve the immunogenicity particularly against DENV-2.